Autour de Polanyi : vocabulaires, théories et modalités des échanges - Clancier, P.; Bresson, Alain (Editions De Boccard, 2005)
The varied questions which arise from the contributions made in this work provide a new modernity to Karl Polanyi and show the major interest in bringing together, as openly as his own, the various historical and economic specialties , Archaeological, ethnological, present in the House of Archeology and Ethnology of Nanterre. One of the most stimulating aspects of the contributions gathered here is the importance given to the presence of men, far beyond the simple equation of economic relations. These contributions sweep away a voluntarily vast field, from antiquity to the contemporary world. The historiographical dimension of Karl Polanyi's career is also present, through the contributions of Anne Chapman, who worked with him in South America, and his daughter, Kari Polanyi Levitt, specialist in development economics. Nathalie Zemon Davis, historian of societies in modern Europe, was asked to present the general conclusions of this symposium. Collection Conferences of Archaeology & Ethnology Maison René-Ginouvès , n o 1
History
Keywords: CHAPMAN; Anne; POLANYI LEVITT; Kari; ZEMON DAVIS; Nathalie

Karl Polanyi et la séparation institutionnelle entre politique et économie - Buğra, Ayşe (Raisons politiques, 2005)
This article explores Karl Polanyi’s analysis of the institutional separation of politic and the economy in the context of the 19th century market economy. The contribution his analysis could make to the quest for viable alternatives to the contemporary neo-liberal international order depends on how we construe two key concepts in his work, “disembeddedness” and “countermovement”. In this regard the author suggests that: 1) In Polanyi’s work the disembedded economy appears not as a sociological reality but as a political project, and 2) Polanyi’s analysis of the countermovement does not justify all types of resistance to the market economy as humane and politically acceptable.
Economics; History
Keywords: institutional separation

Le port de commerce : un concept en débat - Graslin, Laetitia; Maucourant, Jérôme (Topoi, 2005)
Economics; History
Keywords: Dahomey and the Slave Trade; port of commerce

Le troc et la monnaie dans la pensée de Polanyi - Maucourant, Jérôme (2005)
Relire K. Polanyi nous affranchit d'une double illusion. Selon la première, l'homme est essentiellement un atome utilitaire exploitant les gains supposés de l'échange, cette vieille « fable du troc » n'étant pas remise en cause par l'économie des « coûts de transaction ». La seconde illusion, construction hétérodoxe voulant s'affranchir de cette fable, attribue à la monnaie les traits d'une institution aussi transhistorique qu'universelle. Certes, de nombreux phénomènes qualifiés de « troc » sont en réalité issus de la destruction d'ordres monétaires. D'ailleurs, K. Polanyi, commentant Aristote, montrait déjà que le dogme de la naturalité du troc est une projection des a priori de la société de marché. Mais, ceci ne signifie pas que la monnaie soit « souveraine » : seules les communautés politiques sont souveraines, seule la réciprocité, au sens de l'école maussienne, est un universel, le troc pouvant être « enchâssé » dans l'économie. Review Polanyi frees us a double illusion. According to the first, man is essentially a utilitarian atom exploiting the supposed gains of exchange, this old "barter fable" not being called into question by the economy of "transaction costs". The second illusion, a heterodox construction wishing to free itself from this fable, attributes to money the features of an institution as transhistorical as a universal one. Certainly, many phenomena called "barter" are in fact derived from the destruction of monetary orders. Besides, K. Polanyi, commenting Aristotle, already showed that the dogma of the naturalness of barter is a projection of a priori of the market society. But this does not mean that money is "sovereign": only political communities are sovereign, only reciprocity, in the sense of the Maussian school, is a universal, barter can be "enshrined" in the economy.
Economics; Political Science
Keywords: barter; universal barter

L'ère de l'opulence selon Polanyi - Maucourant, Jérome; Vivel, Christel (Economies et sociétés, 2005)
L'article expose la problématique d'un texte peu connu de Polanyi datant de 1959. Prétextant un commentaire de L'ère de l'opulence de Galbraith, il soutient que le naturalisme de l'économie dominante nous interdit de comprendre la signification véritable de la rareté. Polanyi montre alors que les oppositions classiques entre liberté et égalité, économie et démocratie, peuvent être dépassées dans le cadre d'une société nouvelle abolissant la séparation institutionnelle de l'économique et du politique. Ces thèses de Polanyi sont imprégnées d'un aristotélisme tenant compte des déchirures sociales que furent le machinisme et les fascismes. KM: One aims at presenting a unknown Polanyi's text. Starting with a comment of the Affluent Society from Galbraith, we explain that the mainstream economics'naturalism prevents us from understanding the actual significance of scarcity. Polanyi shows that the classical oppositions between liberty and equality, economy and democracy can be overcame in the frame of a brand new society in which the institutional line between economics and politics should be abolished. This is sustained by an aristotelism that takes into account the social breaks produced by machinism and fascisms.
Economics; Sociology
Keywords: opulence; rareté

Propos d'Aristote sur une société d'abondance - Polanyi, Karl (Economies et sociétés, 2005)
KM: Translation of a Polanyi essay - involves Michele Cangiani and Jérôme Maucouran. Nous publions ci-dessous la traduction en français d'un texte inédit de Karl Polanyi : « Aristotle on an affluent society » (13 mars 1959, Archives de l'Institut Karl Polanyi d'économie politique, Montréal). Ce texte doit paraître aux Éditions du Seuil, en 2006, dans un recueil intitulé Essais de Karl Polanyi, sous la direction scientifique de Michele Cangiani et Jérôme Maucourant, dans la collection « Économie humaine » dirigée par Jacques Généreux. La version présente de ce texte a été traduite par Laurence Collaud en collaboration avec Michele Cangiani, Jérôme Maucourant et Christel Vivel. Œconomia remercie les Éditions du Seuil ainsi que Jacques Généreux d'avoir autorisé cette publication. We publish the French translation of an unpublished text by Karl Polanyi: "Aristotle on an affluent society" (March 13, 1959, Archives of the Karl Polanyi Institute of Political Economy, Montreal). This text is to be published by Éditions du Seuil in 2006 in a collection entitled Essays by Karl Polanyi, under the scientific direction of Michele Cangiani and Jérôme Maucourant, in the collection "Économie humaine" directed by Jacques Généreux. The present version of this text has been translated by Laurence Collaud in collaboration with Michele Cangiani, Jérôme Maucourant and Christel Vivel. Œconomia thanks Editions du Seuil and Jacques Généreux for authorizing this publication.
N/A
Keywords: ARISTOTLE; CANGIANI; Michele; MAUCOURANT; Jérôme; translation

Dé-penser l'économique sans Mauss et avec Polanyi - Sobel, Richard (L'Homme & la société, 2005)
Political Science
Keywords: MAUSS; Marcel; 1872-1950